Can Japanese agriculture survive? : - Takekazu, Ogura (Agriculture policy research center, 1979)
This book consists of the following many parts: development of basic thoughts on agriculture policy, from the revision of the feudal land tax to the introduction of the property tax, changes in the food situation and food policy, a cchronicle of the agricultural, rural and administractive, agrarian problems and agricultural policy before, analysis of agricultural structure, in conclusion some proposals on Japanese agricultural policy.